Nitrogen deposition increases N2O emission from an N-saturated subtropical forest in southwest China. (December 2018) - Xie, Danni; Si, Gaoyue; Zhang, Ting; Mulder, Jan; Duan, Lei
Abstract: Nitrous oxide ( N2 O) is a major greenhouse gas, with elevated emission being reported from subtropical forests that receive high nitrogen (N) deposition. After 10 years of monthly addition of ammonium nitrate (NH4 NO3 ) or sodium nitrate (NaNO3 ) to a Mason pine forest at Tieshanping, near Chongqing city in Southwest China, the simulated N deposition was stopped in October 2014. The results of soil N2 O emissions monitoring in different seasons during the nitrogen application period showed that nitrogen addition significantly increased soil N2 O emission. In general, the N2 O emission fluxes were positively correlated to nitrate (NO3 − ) concentrations in soil solution, supporting the important role of denitrification in N2 O production, which was also modified by environmental factors such as soil temperature and moisture. After stopping the application of nitrogen, the soil N2 O emissions from the treatment plots were no longer significantly higher than those from the reference plots, implying that a decrease in nitrogen deposition in the future would cause a decrease in N2 O emission. Although the major forms of N deposition, NH4 + and NO3 −, had not shown significantly different effects on soil N2 O emission, the reduction in NH4 + deposition may decrease the NO3 − concentrations in soil solution faster than the reduction in NO3 − deposition, and thus be more effective in reducing N2 O emission from N-saturated forest soil in the future. Graphical abstract: Image 1 Highlights: Effects of increasing/decreasing N deposition on soil N2 O emission were studied. N deposition increases soil N2 O emission from an N-saturated subtropical forest. Soil N2 O emissions were positively correlated to NO3 − concentrations in soil water. Abstract : Soil nitrate availability, other than soil temperature and moisture, is key factor determining soil N2 O emission from an N-saturated subtropical forests.